2008
DOI: 10.1002/pon.1311
|View full text |Cite
|
Sign up to set email alerts
|

The counsellees' view of an unclassified variant in BRCA1/2: recall, interpretation, and impact on life

Abstract: Objective: Unclassified variants (UVs, variants of uncertain clinical significance) are found in 13% of all BRCA1/2 mutation analyses. Little is known about the counsellees' recall and interpretation of a UV, and its psychosocial/medical impact.Method: Retrospective semi-structured interviews with open questions and five-point Likert scales were carried out in 24 counsellees who received a UV result 3 years before (sd ¼ 1:9).Results: Sixty-seven percent (16/24) recalled the UV result as a non-informative DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
136
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(142 citation statements)
references
References 56 publications
(69 reference statements)
5
136
0
1
Order By: Relevance
“…Interestingly, Whitmarsh et al (2007) revealed that families view genetic diagnoses in both a positive and/or negative light (often simultaneously), and parents were open to the uncertainties that come with these diagnoses (Whitmarsh et al 2007). There have also been studies to further understand parental perceptions of Bunknown^genetic results by assessing the impact of indeterminate newborn screening results and VUS genetics results in the cancer realm (Aatre and Day 2011;Ardern-Jones et al 2010;O'Neill et al 2009;Vos et al 2008). These studies support an underlying theme: diagnostic uncertainty is an ongoing learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Whitmarsh et al (2007) revealed that families view genetic diagnoses in both a positive and/or negative light (often simultaneously), and parents were open to the uncertainties that come with these diagnoses (Whitmarsh et al 2007). There have also been studies to further understand parental perceptions of Bunknown^genetic results by assessing the impact of indeterminate newborn screening results and VUS genetics results in the cancer realm (Aatre and Day 2011;Ardern-Jones et al 2010;O'Neill et al 2009;Vos et al 2008). These studies support an underlying theme: diagnostic uncertainty is an ongoing learning process.…”
Section: Introductionmentioning
confidence: 99%
“…Some individuals testing negative for adenomatous polyposis coli mutations predisposing to FAP refuse to be reassured by their negative result and do not believe they are thereby freed from the family curse of early, increased predisposition to colon cancer [5]. We have a convincing illustration in the Vos et al study [6] that contradictory ideas co-exist among women receiving results showing a variant of uncertain significance. In that study,…”
mentioning
confidence: 74%
“…We have a convincing illustration in the Vos et al study [6] that contradictory ideas co-exist among women receiving results showing a variant of uncertain significance. In that study, many women with such results had two independent recollections, 'a factual recollection of an uncertain result and a subjective interpretation that implies a genetic predisposition'.…”
mentioning
confidence: 99%
“…12-15 Such misunderstandings may affect medical decisions, such as prophylactic surgery after disclosure of unclassified variants. 16 Moreover, sound terminology is sine qua non for the unrestrained scientific development and dissemination of genetic knowledge, especially in the light of the persistent increase of the number of articles on NPDTRs.Words are important instruments for the genetic counselor, whose main task is transmitting information about inheritance, DNA-test results, and possible management options. The specific wording may influence how patients and other professionals understand, interpret, memorize, and attach consequences to the result.…”
mentioning
confidence: 99%
“…[12][13][14][15] Such misunderstandings may affect medical decisions, such as prophylactic surgery after disclosure of unclassified variants. 16 Moreover, sound terminology is sine qua non for the unrestrained scientific development and dissemination of genetic knowledge, especially in the light of the persistent increase of the number of articles on NPDTRs.…”
mentioning
confidence: 99%